The Great Race : the amazing Round-the-World Auto Race of 1908 - Blackwood, Gary L. 4 0 16; 5 (New York : Abrams Books for Young Readers, 2008)
Provides an account of the news-making contest to be the first to travel from New York to Paris by automobile, a race launched from four countries in 1908,and includes photographs, illustrations, and profiles of competitors.
Maps on endpapers.
Includes bibliographical references (p. 130-131) and index.
8.8;5-8;5-8.
Keywords: 2 -- 0; 6; History;Juvenile literature. -- Automobile racing;Great race (1908) -- 20th century -- Juvenile literature; 20; 2